Analysis of Rice Field Cluster in Indonesia as an Evaluation of Food Production Availability Using Fuzzy C-Means - Heru Setiono; Totok M Dianto (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Rice fields area in Indonesia is getting narrower every year with the rampant construction of housing and buildings. It results in lower availability of food production hence to meet the needs we have to import rice from other countries. By clustering rice fields, it can be used as an evaluation material to increase food production in Indonesia so that the need for rice imports can be minimized. The method used in the grouping of Rice Fields is the Fuzzy C-means method, implementation of the Knime Tool with data training and testing. The Fuzzy C-Means program produces three data groups/clusters, namely wide, moderate, and narrow rice fields. The results of the clustering show that the most potential areas for food production from rice fields are East Java, Central Java, and West Java.